KKN Tematik STTW 2025: Penerapan Mesin Pencacah Pakan untuk Meningkatkan Efisiensi Peternak Polokarto - Daniel Tabah Pamungkas; Aji Ahmad Fazan; Ambrosius Surya Widi Admaja; Rendy Galang Putra Artian; Tegar Wahyu Praseptiaji; Alfendi Wahyu Budi Laksana; Iqbal Cahyo Nugroho; Fahrizky Aditya Firmansyah; Dhamar Ahmad Diannur; Ghilang Sihno Djati; Dicky Isnan Nur Huda; Bayutri Suryanto; Edy Suryono (Abdi Masya, 2026)
Feed availability is an important factor in supporting the productivity of small-scale livestock farming. However, the process of chopping forage feed in Polokarto Village, Polokarto District, Sukoharjo Regency, was still carried out manually, requiring considerable time and labor while producing non-uniform feed sizes. This community service activity aimed to implement appropriate technology by developing a forage chopper to improve feed preparation efficiency for local livestock farmers. The implementation method consisted of problem identification, machine design and fabrication, performance testing, operational training, and community assistance. The developed forage chopper machine was powered by a 5.5 HP Alkon 160 engine and used a pulley-and-V-belt transmission system. Performance testing showed that the machine achieved an average chopping capacity of 126.7 kg/h. The implementation of the machine increased feed processing capacity from approximately 35 kg/h to 126.7 kg/h, representing a 262% improvement, and reduced the time required to process 100 kg of forage from 180 minutes to 45 minutes, resulting in a 75% increase in efficiency. In addition to improving feed preparation efficiency, the training and mentoring activities enhanced the community's knowledge and skills in operating and maintaining the machine independently. The results indicate that implementing appropriate technology, such as a forage chopper, provides technical, economic, and social benefits for the community while supporting improvements in livestock productivity in Polokarto Village.